2014
DOI: 10.2147/ahmt.s67943
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of health care transition voiced by young adults with type 1 diabetes: a qualitative study

Abstract: ObjectiveThis qualitative study aimed to explore the experience of transition from pediatric to adult diabetes care reported by posttransition emerging adults with type 1 diabetes (T1D), with a focus on preparation for the actual transfer in care.MethodsTwenty-six T1D emerging adults (mean age 26.2±2.5 years) receiving adult diabetes care at a single center participated in five focus groups stratified by two levels of current glycemic control. A multidisciplinary team coded transcripts and conducted thematic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
153
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(161 citation statements)
references
References 39 publications
(48 reference statements)
6
153
2
Order By: Relevance
“…This is in contrast to several studies of emerging adults who have reported a lack of purposeful transition preparation 20 and dissatisfaction with the transition process within the pediatric care setting. 3 4 15 Patients with inadequate transition preparation are at a higher risk for gaps >6 months between the last pediatric and first adult care visit.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to several studies of emerging adults who have reported a lack of purposeful transition preparation 20 and dissatisfaction with the transition process within the pediatric care setting. 3 4 15 Patients with inadequate transition preparation are at a higher risk for gaps >6 months between the last pediatric and first adult care visit.…”
Section: Discussioncontrasting
confidence: 99%
“…4,9 The patients in our study reported saving over 6 h from their work or school day by completing their diabetes clinic visit virtually, which may improve adherence with routine diabetes care appointments. Offering the opportunity to interact with healthcare providers via Professionally led support groups have shown potential to improve diabetes self-care behaviors and reduce diabetes distress for young adult patients in their 20s.…”
Section: Discussionmentioning
confidence: 77%
“…3,4 Additionally, young adults with diabetes have a high risk of diabetic ketoacidosis (DKA), diabetes complications, and diminishing mental health, 1,2,5-8 making them a population in need of support.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations